Self-reported sexual coercion among in-school young people with disabilities in Ghana - Abdul-Aziz Seidu; Akwasi Kumi-Kyereme; Eugene K. M. Darteh (BMC, 2024)
Abstract Background Sexual coercion is one of the major public health concerns globally. This is even more worrying among young people with disabilities (YPWDs). This study assessed the prevalence and factors associated with sexual coercion among in-school young people with disabilities in Ghana. Methods Using a cross-sectional study design, pre-tested questionnaires were used to collect data from 979 YPWDs in 15 special schools for the visually and hearing impaired in Ghana. Sexual coercion was the outcome variable. Both descriptive (frequencies and percentages) and inferential analysis (binary logistic regression) were conducted. Results About 68% reported that they had been sexually coerced at some point in their lifetime. This was higher among males (69.9%) compared to females (66.8%). Those aged 15-19 (72.19%) had the highest prevalence compared to those aged 20-24 (61.74%). YPWDs in Junior High School [JHS] [aOR = 1.722; CI = 1.227,2.417], and those in the coastal zone [aOR = 1.616; CI = 1.068,2.443] had higher odds of being coerced. However, those belonging to the Islamic religion [aOR = 0.266; CI = 0.0764,0.928] and the visually impaired [aOR = 0.477; CI = 0.318,0.716] had lower odds of being coerced compared to those with no religion, and the hearing impaired, respectively. Conclusion There is a relatively high prevalence of sexual coercion among in- school YPWDs in Ghana. This is significantly associated with level of education, ecological zone, religion, and the type of disability. This calls for a concerted effort by policy makers such as the Ghana Education Service, Ghana Federation of the Disabled, Ministry of Education, Ministry of Gender, Children and Social Protection to intensify sex education and put in pragmatic steps to halt this serious public health issue.